An Investigation of Brain-Based Learning Principles in Today's Changing Conditions - Burak Can Korkmaz (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The increasing prevalence of brain research and the fact that the findings reveal important arguments about the learning process have led to the proliferation of brain-based learning studies. Brain-based learning principles, introduced by Caine and Caine in 1991, are frequently used in the literature and shed light on educational research. However, in today's changing conditions, educational environments have remarkably differentiated, the opportunities for learners have increased more than ever before, threats such as the Covid-19 pandemic and natural disasters have directly affected education, and technological advances have made a breakthrough with artificial intelligence. There are studies evaluating 12 accepted and frequently used brain-based learning principles in the literature, but there is no review study that addresses brain-based learning principles in today's changing conditions. Therefore, this article aims to examine the principles of brain-based learning in today's changing conditions. Increasing threats in the rapidly changing world pose a risk to brain-based learning. Also, increasingly common helicopter parenting and artificial intelligence hinder brain-based learning, although they have some advantages. However, on the other hand, the fact that technological developments make educational environments richer and increase the opportunities for learners greatly facilitates brain-based learning. Thus, brain-based learning principles have become much more meaningful and gained great importance in today's world.